Micronuclei frequencies in oral mucosal cells in patients undergoing nickel-titanium orthodontic archwires therapy - Erdem, Onur; Çetinkaya, S.; Kaplan, M.; Çırak, Eyüp; Gökçe, Sıla Mermut; Akay, Cemal (Elsevier Reland, 2015)
Nickel(Ni)andtitanium(Ti),primarycomponentsoforthodonticappliances,areroutinelyusedinorthodontictreatmentinrecent years.However,littleisknownaboutthepossiblegenotoxiceffects oftheseapplianceswithrespecttochildrenevaluatingassensitive group. Thus, the aim of this study was to investigate the genotoxiceffectsof?xedorthodonticappliancesinasampleofchildren patients undergoing orthodontic appliances with micronucleus (MN) test. In this study, right and left buccal epithelial cells were collectedfromatotalof32patientsbeforeplacementand7th,15th and 30th days after placement of ?xed appliances.
51st Congress of the European-Societies-of-Toxicology (EUROTOX) -- September 13-16, 2015 -- Portuguese Soc Pharmacol, Sect Toxicol, Porto, Portugal
WOS: 000370693801269
Keywords: Micronuclei; Mucosal; Orthodontic